Potensi Pengembangan Biodiesel Kelapa Sawit dengan Katalis Limbah Udang di Sumatera Selatan - Siti Khodijah; F. Irsan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Khodijah S, Irsan F. 2020. Development potential of oil palm biodiesel with shrimp waste catalysts in south Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Oil Palm is one of agriculture commodity with huge areal dan production potencial in Indonesia. Oil palm biomass has been developed a lot as fuel such as Crude Palm Oil biodiesel. At the transesterification process, commonly using strong alkaline (NaOH and KOH) or strong acid (H2SO4 and HCl) as homogenous catalyst. Heterogeneous catalyst can be used in transesterification process instead of homogenous catalyst, one of them is CaO catalyst. The purpose of this paper is to know the development potential of oil palm biodiesel with CaO catalyst from shrimp waste in South Sumatra. The biodiesel product was analyzed with density, viscosity, flash point, acidity, refractive index, and calorific values. The quality of biodiesel product ie, Density 0,8666 g/ml, Viscosity 5,4982 cSt, Flash point 161 ° C , Acid Numbers of 0.2204 mg-KOH/ g, and the Bias Index of 1.4480, which has qualified Indonesia National Standart requirement for biodiesel product with the development potential of CaO catalyst from shrimp waste as much as 2,834-4,048 tonne in South Sumatra.